PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI - Kahuningan, Anak Agung Sagung Pradnyasita; Netra, I Gusti Salit Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
Compensation is an important aspect for a company. This study aims to determine the effect of compensation on employee performance with motivation as a mediating variable at PT. Astra International Tbk. Daihatsu Cokroaminoto Branch, Denpasar. This research was conducted by PT. Astra International Tbk. Daihatsu Cokroaminoto Branch, Denpasar involving all 55 employees using the saturated sample or census method. Primary data collection is done by using a questionnaire. The results of the respondents' answers were continued with validity and reliability tests, then continued with hypothesis testing using path analysis and sobel tests. The results of the analysis show that compensation has a positive and significant effect on employee performance, compensation has a positive and significant effect on motivation, motivation has a positive and significant effect on employee performance, compensation has a positive and significant effect on employee performance with motivation as the mediating variable. The results of this study provide implications for the theory of expectation to PT. Astra International Tbk. Daihatsu Cokroaminoto Branch to pay more attention to compensation to improve employee performance and motivation